\(a,\Leftrightarrow\left\{{}\begin{matrix}6x-9y=-15\\-6x+8y=4\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}2x-3y=-5\\-y=-11\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=\dfrac{-5+33}{2}=14\\y=11\end{matrix}\right.\)
b: \(\left\{{}\begin{matrix}2x-3y=-5\\-3x+4y=2\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}6x-9y=-15\\-6x+8y=4\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}-y=-11\\2x-3y=-5\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=11\\x=\dfrac{-5+3y}{2}=\dfrac{-5+3\cdot11}{2}=14\end{matrix}\right.\)